2016
DOI: 10.5194/bg-13-27-2016
|View full text |Cite
|
Sign up to set email alerts
|

Detection and spatiotemporal analysis of methane ebullition on thermokarst lake ice using high-resolution optical aerial imagery

Abstract: Abstract. Thermokarst lakes are important emitters of methane, a potent greenhouse gas. However, accurate estimation of methane flux from thermokarst lakes is difficult due to their remoteness and observational challenges associated with the heterogeneous nature of ebullition. We used high-resolution (9-11 cm) snow-free aerial images of an interior Alaskan thermokarst lake acquired 2 and 4 days following freeze-up in 2011 and 2012, respectively, to detect and characterize methane ebullition seeps and to estima… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 43 publications
2
35
0
1
Order By: Relevance
“…To further characterize the sources of whole‐lake CH 4 emissions, we utilized an iterative four‐source mass balance model (equation ) to estimate the range of possible contributions from four key C reservoirs in GSL. The four 14 C end‐members were chosen based on the distinct seep types characterized by Lindgren et al () and Walter Anthony and Anthony () and previously surveyed in a comprehensive study ( n = 30). Seep categories included tiny seeps 120 ± 40 YBP ( n = 1, analytical error only), A and B seeps (combined in this plot) 2,710 ± 2590 YBP ( n = 5), C seeps 11,200 ± 3,250 YBP ( n = 3), and weaker hotspot seeps still susceptible to blockage by winter ice 13,740 ± 3,160 YBP ( n = 21).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further characterize the sources of whole‐lake CH 4 emissions, we utilized an iterative four‐source mass balance model (equation ) to estimate the range of possible contributions from four key C reservoirs in GSL. The four 14 C end‐members were chosen based on the distinct seep types characterized by Lindgren et al () and Walter Anthony and Anthony () and previously surveyed in a comprehensive study ( n = 30). Seep categories included tiny seeps 120 ± 40 YBP ( n = 1, analytical error only), A and B seeps (combined in this plot) 2,710 ± 2590 YBP ( n = 5), C seeps 11,200 ± 3,250 YBP ( n = 3), and weaker hotspot seeps still susceptible to blockage by winter ice 13,740 ± 3,160 YBP ( n = 21).…”
Section: Resultsmentioning
confidence: 99%
“…For GSL only, annual ebullition rates were estimated by quantifiying the density of predefined ebullition seep types (A, B, C, and Hotspot) using ice-bubble surveys as in Walter Anthony and Anthony (2013). A fifth seep type, known as tiny seeps, which are small, widely dispersed, and unmerged in lake ice (Greene et al, 2014;Lindgren et al, 2016), were also quantified. Walter Anthony and Anthony (2013) also show the locations of these surveys on GSL, which covered aproximately 10% of the lake area.…”
Section: Quantification Of Annual Ebullition Rates On Gslmentioning
confidence: 99%
“…In another type of remote sensing application, Lindgren et al . () used low‐altitude aerial photographs to map and quantify methane ebullition features in lake ice in interior Alaska and found that higher methane‐seep densities occurred along lake shores with higher erosion rates, signalling a direct linkage between permafrost thaw along thermokarst lake margins and decomposition of previously frozen soil carbon.…”
Section: Permafrost Degradationmentioning
confidence: 99%
“…Determining annual sea‐air CH 4 flux is complicated by ice cover, which impedes and collects CH 4 emissions for much of the year and may contribute to enhanced flux at ice‐out. These processes have been observed in lakes [ Greene et al , ; Jammet et al , ; Lindgren et al , ].…”
Section: Introductionmentioning
confidence: 99%